ANALISIS STATISTICAL QUALITY CONTROL (SQC) PADA INDUSTRI RUMAH TANGGA MASYITAH BAKERY - Ayu Anggraeni; Fadjriyani Fadjriyani; Dwiky Rahmat Darmawan (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2020)
Abstract This research aims to identify the type of damage that often occurs in the product of pastry and bread household industry Masyitah Bakery, as well as analyzing the application of the SQC method in controlling product quality. Data is the primary data obtained from the observation on the site of the pastry and bread business Masyitah Bakery. The sample of data is taken per day within 14 days. Further data is analyzed using the Statistical Quality Control (SQC) method. The first thing to do is to create a Check Sheet, then analyze the types of errors that often occur using Pareto diagrams. After that to see if the production process is still under control, then analysis is done by using the control map. After that the data is analyzed by using a causal diagram to find out the cause of product damage that often occurs. Based on the results of the analysis, then get the result that the most common damage to the production process Masyitah Bakery is burnt defects with a percentage of 44.04 percent, then size defects do not correspond to the percentage of 37.6 percent and the texture defects do not correspond to a percentage of 22.0 percent. The damage caused by the lack of labor, inadequate machinery and raw materials that are not as standard. Judging from the control map formed, the quality of products Masyitah Bakery is still within the control limit. However some points almost close to the control limit line, so it is necessary to control the production process. For example, with more attention to the feasibility of every tool used as well as labor skills employed.